Methods of accelerating chloride-induced corrosion in steel-reinforced concrete: A comparative review. (28th June 2021) - Feng, Weipeng; Tarakbay, Anel; Ali Memon, Shazim; Tang, Waiching; Cui, Hongzhi
Highlights: Three main accelerated corrosion methods for steel-reinforced concrete were reviewed. Comparative evaluation of each method had been done in terms of main input parameters. Corrosion products and mass loss for the methods were comprehensively discussed. Abstract: Rebar corrosion has been recognized as a major durability issue of the reinforced concrete (RC) structures over recent decades, prompting the necessity to study the corrosion behavior of steel in concrete during the service life. To estimate service life of RC structure, the corrosion of reinforcing steel is generally accelerated by means of the impressed current technique in limited available time. In the literature, several accelerated laboratory corrosion methods have been proposed, however the results varied greatly as chloride concentrations and testing conditions were different. Researchers are unsure which testing methods can be used to give reliable results to simulate the real-life corroded RC structure. This review paper aims to systematically compare and evaluate different methods of accelerating chloride-induced corrosion of steel reinforcement in concrete. First, the accelerated methods categorized into three groups namely, the impressed current (IC), the chloride ion diffusion (CID) and the artificial climate environment (ACE) are briefly discussed. Then, the key influencing factors (i.e. current density, salt concentration, service load) affecting the corrosion results in different methods are compared and evaluated. Finally, the corrosion products and acceleration method are comprehensively discussed. By this comparative review, it is believed that researchers can have a better understanding of different accelerated corrosion methods along with the influencing factors. So they could select or even develop the most suitable techniques to yield reliable corrosion test results.